ANALISIS HASIL PREDIKSI MAGNITUDO GEMPA DI WILAYAH KOTA PADANG MENGGUNAKAN TEKNIK RANDOM FOREST - Ade Fauzan; Defri Ahmad (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The topic of earthquake prediction is an interesting one to research. As one of the natural disasters, earthquakes are included in natural disasters that can cause considerable damage. The damage caused not only affects the economy but also the life of an area. Several studies on earthquake prediction have been conducted so far, one of which is Machine Learning and using the Random forest method. The purpose of the research is to determine the analysis of earthquake magnitude prediction results in the Padang City area using machine learning techniques. The variables used in this study are time, latitude, longitude, and magnitude. Earthquake data is obtained from the United States Geological Survey (USGS) website. This research produces an RMSE value of 0.31758 and an MSE value of 0.10085